Transition from e-government to digital government: A case study of the Revenue Department, Department of Land Transportation and Department of Rural Roads - Keawwisut, Suparat; Noranitipadungkarn, Chakrit (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aims to 1. study the transition of the Thai public administration system from e-government to digital government in terms of public service delivery, 2. study problems and obstacles in the delivery of public services. 3. compare the effects of the transition from e-government to digital government that affects the delivery of public services; 4. study the development of government services that affect the delivery of public administration. The research methodology used a qualitative case study approach, with in-depth interviews from 3agencies: The Revenue Department, The Department of Land Transport and The Department of Rural Roads The research findings were as the following: 1) the transition from e-government to a digital government has resulted in the delivery of public services becoming more convenient, efficient, and time-saving. The previous approach required individuals to fill out forms and physically visit government agencies to request services. With the new digital format, service recipients can now carry out various transactions through platforms such as Line, leading to increased convenience, speed, time efficiency, and cost-effectiveness in service requests. 2)The transition from e-government to digital government has problems and obstacles as follows:(1) Problems in information technology readiness and budget (2) The problem of creating understanding and coping with changes among operators and service users (3) Problems in integrating and linking information with other sectors (4) Legal limitations that are not conducive to development; and (5) Lack of personnel with expertise in information technology system development and service personnel. 3)The comparison of the transition from e-government to a digital government, regarding the impact on the delivery of public services by three government agencies, reveals that they are aligned and moving in the same direction. The transition is characterized by service improvement and the integration of technology in the provision of public services to the general public, private sector, and others. There is also a consolidation of data connectivity among government agencies. 4) Development guidelines focus on enhancing the skills and knowledge of personnel through training and knowledge-sharing initiatives. This approach is essential to address the common issue identified in all three case studies, where the majority of the workforce lacks job-specific skills in service-oriented tasks and there is a shortage of specialized experts. Additionally, the management of knowledge within the organization needs improvement to facilitate collaborative innovation.Keywords:Transition, E-government, Digital government, public service Article history: Received 9 May 2023 Revised 11 June 2023 Accepted 12 June 2023 SIMILARITY INDEX = 2.32 %